SISTEM PENGUSAHAAN USAHATANI SEMANGKA DI LAHAN PASIR : APAKAH MENGUNTUNGKAN? - Aditya Sasongko; Djoko Soejono (JSEP (Journal of Social and Agricultural Economics), 2021)
Agricultural land in the agriculture sector has decreased. One alternative that can be done is to expand the agriculture area to marginal land, namely coastal sand land. One of the commodities that can be cultivated in sandy land is watermelon. This study aims to determine the cultivation system, farmers' income, cost efficiency, and factors that affect the income of watermelon farming in the sandy land of Paseban Village. This research method was descriptive-analytic with data analysis use analysis of income, cost efficiency, and multiple linear regression. The results showed that 1) The watermelon farming system consists of upstream subsystems, watermelon farming, and downstream subsystems, but the watermelon farming systems are not supporting by supporting institutions. 2) Based on calculations from analysis of income and efficiency, the results of watermelon farming in the sand land are detrimental within an average farmer's income of -Rp671,116.47 and an efficiency level of 0.9709. 3) The factors that affect watermelon farming have fulfilled the classical assumption test with the result that 93.3% of the tested factors affecting farmer's income. The factors that have a significant effect are selling price, labor, and production, while the insignificant factors are fertilizers, pesticides, and land area.